Research Progress on Photocatalytic Reduction of Cr(VI) in Polluted Water - Yuan, Gaoqian; Li, Faliang; Li, Kezhuo; Liu, Jie; Li, Junyi; Zhang, Shaowei; Jia, Quanli; Zhang, Haijun (Bulletin of the Chemical Society of Japan, 2021)
More and more wastewater containing hexavalent chromium (Cr(VI)), which causes increasingly threatening environmental events including death of plants or organisms, soil inactivation and canceration of human organs, has been caused by rapid industrial growth. Various methods, such as photocatalytic reduction, physical adsorption, electrochemical and photoelectrochemical approaches have been proposed to detoxify/remove Cr(VI) contained in wastewater. Quite significantly, photocatalytic Cr(VI) reduction grabs increasing attention with many advantages, including environmental friendliness, no sludge, low secondary pollution risk, high utilization of solar energy and low dosage of chemical reagents. For the purpose of improving the Cr(VI) removal efficiency during the photocatalytic reduction process, various kinds of catalysts were developed. In this mini-review, the photocatalytic reduction of Cr(VI) by ion doping photocatalysts, faceted photocatalysts, and heterostructure photocatalysts are briefly introduced. Furthermore, some suggestions for modifying photocatalysts to enhance their photocatalytic performance on Cr(VI) reduction are put forward.